Plastic deformation of a Zr-based bulk metallic glass fabricated by selective laser melting - Deng, Liang; Kosiba, Konrad; Limbach, R.; Wondraczek, Lothar; Kuehn, U.; Pauly, S. (Journal of Materials Science & Technology, 2021)
Fully amorphous Zr52.5Cu17.9Ni14.6Al10Ti5 bulk metallic glass (BMG) samples with a relative density exceeding 98% were fabricated via selective laser melting (SLM). High fracture stresses of around 1700 MPa and a reproducible plastic strain of about 0.5% were obtained for cylindrical SLM samples. The analysis of the observed serrations during compressive loading implies that the shear-band dynamics in the additively manufactured samples distinctly differ from those of the as-cast glass. This phenomenon appears to originate from the presence of uniformly dispersed spherical pores as well as from the more pronounced heterogeneity of the glass itself as revealed by instrumented indentation. Despite these heterogeneities, the shear bands are straight and form in the plane of maximum shear stress. Additive manufacturing, hence, might not only allow for producing large BMG samples with complex geometries but also for manipulating their deformation behaviour through tailoring porosity and structural heterogeneity.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Bulk metallic glass; Heterogeneity; Powder bed fusion; Selective laser melting; Serrated flow